2010
DOI: 10.3109/08860221003759478
|View full text |Cite
|
Sign up to set email alerts
|

The effects of polymicrobial sepsis with diabetes mellitus on kidney tissues in ovariectomized rats

Abstract: Objectives: Sepsis model was used to understand the role of sustained hyperglycemia and ovariectomy, either separately or concomitantly, on the response of the activity of the nuclear factor kappa B (NF-kB) and the oxidative response in kidney. Subjects: Polymicrobial sepsis was induced by cecal ligation and puncture (CLP). Diabetes was induced in female rats using administration of alloxan. The rats were divided into five groups: sham control (group 1), ovariectomy (group 2), ovariectomy + sepsis (group 3), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 49 publications
0
8
0
2
Order By: Relevance
“…Mortality increased gradually with the puncture size, from 27% with a 22-gauge needle to 95% with the blade incision during a week of observation [38]. In addition, in our previous studies we observed mortality within 12-20 h after sepsis induction with a 12-gauge needle [39][40][41][42]. However, in studies performed with 21-and 22-gauge needles, mortality was not as common [38,43,44].…”
Section: Sepsis Modelmentioning
confidence: 80%
See 1 more Smart Citation
“…Mortality increased gradually with the puncture size, from 27% with a 22-gauge needle to 95% with the blade incision during a week of observation [38]. In addition, in our previous studies we observed mortality within 12-20 h after sepsis induction with a 12-gauge needle [39][40][41][42]. However, in studies performed with 21-and 22-gauge needles, mortality was not as common [38,43,44].…”
Section: Sepsis Modelmentioning
confidence: 80%
“…ROS have been assumed to play a role in the induction of many proinflammatory cytokines and mediators important in producing the acute inflammatory responses associated with sepsis [12]. In our previous studies we determined that kidney, heart, lung and liver tissue exhibited oxidative stress in septic rats [40][41][42]. The proinflammatory effects of ROS include endothelial damage, formation of chemotactic factors, neutrophil reinforcement, cytokine release and mitochondrial injury [14][15][16], which all contribute to free radical overload and to oxidant-antioxidant imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α provokes neutrophil-mediated tissue injury by acting on endothelial cells and neutrophils. A primary role for TNF-α in sepsis is also suggested by several studies conducted on cell lines, animal models, and human beings [15,31,32,33,34,35,36]. TNF-α activates IL-6, which is an important mediator in septic shock and a marker of proinflammatory cytokine activation, and is also defined as an early predictor of organ dysfunction.…”
Section: Discussionmentioning
confidence: 95%
“…All these studies and our findings suggest an increased iNOS expression during diabetes-induced brain damage, and bosentan treatment decreased iNOS expression as a protective mechanism against this damage. Likewise, it was shown that oxidative stress increased in many organs, dependent on diabetes [54,55]. A previous study showed the superoxide scavenger effect of the superoxide dismutase enzyme in cerebral arterioles dependent on type 1 diabetes [56].…”
Section: Discussionmentioning
confidence: 99%